Cellulose‐reinforced catechol‐modified polyacrylic acid‐Zn2+ coacervate as strong composite adhesive. Issue 9 (16th October 2018) - Li, A.; Xu, Z.; Sun, N.; Si, Z.; Xu, Y.; Guo, X.
ABSTRACT: By secreting adhesive mussel foot protein, an ingenious strategy was developed based on marine mussels to adhere to rocks firmly under severe dash of seawater, which inspires researchers to develop a series of novel biomimetic adhesives, and distinguished bonding strength has been achieved. Here, on the basis of polyacrylic acid‐DOPA/Zn 2+ adhesive coacervate, cellulose fibers or nanocrystals were introduced into the adhesive system as fillers to increase the cohesion of the adhesive by forming van der Waals interactions with the gel. By optimizing the amount of the fillers, length as well as the type of the fillers, bonding strength up to above 10 MPa comparable to commercial glues was achieved on aluminum substrates, which is found to be superior than most of the mussel‐inspired adhesives. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47126. Abstract :